Przemiany kulturowe w XIII wieku na Pomorzu Wschodnim i zagadnienie kolonizacji na prawie niemieckim - Kmieciński, Jerzy (Acta Universitatis Lodziensis. Folia Archaeologica, 1989)
The social-economic changes undergoing in the XIIIth century Europe had an influence upon the development of old and the creation of new municipal centres. This phenomenon brought about the new way of town foundation (according to Magdeburg and Lübeck law) and also about the new colonization related with it. The hitherto existing literature of the subject has treated casually the problem of cultural changes which were followed by colonization processes. However, the colonization process is of great methodological value especially for the studies on cultural changes and on the ethnic interpretation of archeological sources. On the basis of three variants of the course of this process i.e.: • the settlement of foreign immigatorv population in the new place, • rehousing of the local population according te the German law, • the settlement of foreign immigrants in existing rural and town communities, three different models of cultural changes can be observed. Such organized and arranged model investigations are led by a group of workers of University of Łódź in the chosen region of East Pomerania. The region chosen for this gave the opportunity to observe the traditional structuras of the settlement and also provided with materials undoubtedly related to immigratory groups of population. The area of castellany of Raciąż in the Duchy of Świecko was chosen for the research. Investigations concentrated upon the XIIIth century castle (made of earth and wood) of Raciąż castellany and upon municipal settlement in Tuchola. These studies proved that Raciąż, the castellanian abode, both in respect to fortification and interior buildings and in respect to the archeological material found in layers presents typical features for the Western Slavs. It is also reflected in the written sources. Whereas, Tuchola is characterized by the typical arrangement of the town settled according to the German law (what is confirmed by documents) and also by the totally different representation of the material culture what indicates on the immigration of the new foreign population. It seems that in the discursed case the first model of the course of the colonization process i.e. the settlement of foreign population in oreder to cultivate the land and also to introduce new production techniques is observed.